Static Electricity Material E-Module Based on a Scientific Approach Using Kvisoft Flipbook Maker Software - Aggraini, Rini; Patmi, Patmi (Program Magister Teknologi Pendidikan Universitas Jambi, 2015)
The availability of adequate teaching materials can make it easier for students to study independently and overcome problems that often occur in classroom learning. This research aims to determine students' perceptions of Electronic Modules based on a Scientific Approach using Kvisoft Flipbook Maker Software on Static Electricity Material for the Basic Physics 1 course which has been developed. The research design used is Research and Development (R & D). This research is only limited to the research and development stage. This research was conducted at the Physics Education Study Program, FKIP, Jambi University in March 2018. This research data was obtained by distributing questionnaires to the 2015 Physics Education students of the PGMIPAU class. The research results show that the Electronic Module based on a scientific approach that has been developed has met the feasibility criteria very well in terms of 3 aspects, namely the module appearance aspect, the module presentation aspect, and the module benefits aspect with an average score of 5.68 respectively; 4.87 and 13.45. The average score for all student perception indicators is 49.95 in the very good category.